Appropriate levels of natural sounds to enhance soundscapes in urban areas - Hong, Joo Young (2025)
This study aims to investigate optimal sound levels of natural sounds to mask noise sources and to increase overall preference of sound environment. Road traffic and construction noises were used as urban noises. Natural sounds including bird and stream sounds were selected as positive soundscape maskers for the urban noises. Laboratory experiments were performed to determine the ranges of masking-to-noise ratio (MNR) between natural sounds and urban noises to achieve lower perceived loudness of traffic noise and higher soundscape quality. The urban noises were set to three different noise levels, 55, 65 and 75 dB, and the noise source combined with natural sounds were created with varying MNR from -6 dB to +6dB for the experiments. Perceived loudness of noise and pleasantness of soundscape for the acoustic stimuli were evaluated in experiment I. Paired comparison method was applied to discriminate the preference levels across the MNRs at different noise levels. The results showed that natural sound can reduce the perceived loudness of noise and the masking effects were found between MNR of -6 and -3dB. In addition, natural sound also improved the overall soundscape equality, but acoustical characteristics of noise source affect the preference of maskers.